2017
DOI: 10.1016/j.jpba.2017.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fingerprinting of principal neurons in the rodent hippocampus: A neuroinformatics approach

Abstract: Neurons are often classified by their morphological and molecular properties. The online knowledge base Hippocampome.org primarily defines neuron types from the rodent hippocampal formation based on their main neurotransmitter (glutamate or GABA) and the spatial distributions of their axons and dendrites. For each neuron type, this open-access resource reports any and all published information regarding the presence or absence of known molecular markers, including calcium-binding proteins, neuropeptides, recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…From this literature, 237 papers showed data indicating expression or lack of expression via immunohistochemistry, in situ hybridization, or single cell RT-PCR in neurons matching the descriptions of Hippocampome.org types based on neurite location and putative neurotransmitter. In addition, we used data from the Allen Gene Expression Atlas as the basis for assigning the presence or absence of certain molecular markers in the principal neuron types DG Granule, CA1 Pyramidal, CA2 Pyramidal, and CA3 Pyramidal (Hamilton et al, 2017). All of these data are considered neuron type-specific evidence and lead to interpretations of positive or negative expression in Hippocampome.org.…”
Section: Obtaining Direct Molecular Expression Evidencementioning
confidence: 99%
“…From this literature, 237 papers showed data indicating expression or lack of expression via immunohistochemistry, in situ hybridization, or single cell RT-PCR in neurons matching the descriptions of Hippocampome.org types based on neurite location and putative neurotransmitter. In addition, we used data from the Allen Gene Expression Atlas as the basis for assigning the presence or absence of certain molecular markers in the principal neuron types DG Granule, CA1 Pyramidal, CA2 Pyramidal, and CA3 Pyramidal (Hamilton et al, 2017). All of these data are considered neuron type-specific evidence and lead to interpretations of positive or negative expression in Hippocampome.org.…”
Section: Obtaining Direct Molecular Expression Evidencementioning
confidence: 99%
“…Quality check for the scRNA-seq is provided in Figure S2. Clustering using specific gene-set enrichment for cell-type identification (Hamilton, White, Rees, Wheeler, & Ascoli, 2017; Saunders et al, 2018) (Figure 1b) revealed quantitative and qualitative differences in cellular subpopulations between ED and MD. It appears evident that in tissue processed at 37°C there is a higher extent of cell death among sensitive populations, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…We defined dentate gyrus cell types based on the knowledge base Hippocampome.org, an online repository containing morphological, molecular, and physiological information on neurons of the rodent hippocampal formation (Wheeler et al 2015). Hippocampome.org classifies neurons primarily by neurotransmitter released and the presence of axons and dendrites in the distinct sub-regions and layers of the rodent hippocampus ( Figure 1), and also includes molecular biomarker (Hamilton et al 2017) and electrophysiological properties (e.g. Lubke et al 1998) for each type.…”
Section: Classification Schemementioning
confidence: 99%
“…Therefore, the system was both underdetermined and inconsistent. 16 Buckmaster and Jongen-Relo 1999, Table 1 stereology 46, 734 = X 2 + X 4 + X 5 + X 6 + X 12 + X 14 + X 16 Buckmaster and Jongen-Relo 1999, Table 1 stereology 35, 900 = X 6 + X 7 + X 8 + X 9 + X 10 + X 11 + X 12 + X 13 +…”
Section: Equation Generationmentioning
confidence: 99%